Interventions using behavioural insights to influence children's diet‐related outcomes: A systematic review. (19th January 2021) - Chambers, Timothy; Segal, Alexa; Sassi, Franco
Summary: The global prevalence of children with overweight and obesity continues to rise. Obesity in childhood has dire long‐term consequences on health, social and economic outcomes. Promising interventions using behavioural insights to address obesity in childhood have emerged. This systematic review examines the effectiveness and health equity implications of interventions using behavioural insights to improve children's diet‐related outcomes. The search strategy included searches on six electronic databases, reference lists of previous systematic reviews and backward searching of all included studies. One‐hundred and eight papers describing 137 interventions were included. Interventions using behavioural insights were effective at modifying children's diet‐related outcomes in 74% of all included interventions. The most promising approaches involved using incentives, changing defaults and modifying the physical environment. Information provision alone was the least effective approach. Health equity implications were rarely analysed or discussed. There was limited evidence of the sustainability of interventions—both in relation to their overall effectiveness and cost‐effectiveness. The limited evidence on health equity, long‐term effectiveness and the cost‐effectiveness of these interventions limit what can be inferred for policymakers. This review synthesises the use of behavioural insights to improve children's diet‐related outcomes, which can be used to inform future interventions.